Home ranges of Ornate Box Turtles in remnant prairies in north-central Illinois - Struecker, Brock; Muñoz, Andrés; Warcholek, Stanislaw; Harden, Leigh Anne; Milanovich, Joseph (Reptiles & Amphibians, 2023)
Habitat loss has been a primary driver of biodiversity declines throughout the United States. Native prairie ecosystems represent some of the most significant losses in land cover, and subsequently, prairie-dependent species are some of the most imperiled. Therefore, understanding the ecology of species remaining in remnant portions of these ecosystems is important to help manage their populations. Using radio-telemetry, we examined minimum convex polygon (MCP) and 95% kernel density (KD) home ranges of 20 (5 females, 15 males) Ornate Box Turtles (Terrapene ornata) inhabiting two remnant prairies in north-central Illinois across two years and six seasons. Results showed that MCP and 95% KD home range estimates were comparable but smaller than other published studies, differed between years, across seasons, and among individual turtles within sites. These results provide valuable data to quantify the ecology of this threatened species in a remnant prairie habitat.